Some observations in the field of physiology, pathophysiology and pathology of the liver in relation to the problem of jaundice - Urteaga Ballón, Oscar (1943)
We have described in healthy adult subjects, in infants and in many patients the pathology, an oscillation of the two types of bilirubin in the blood twenty-four hours. This oscillation has periods of accumulation and excretion other, each of them, and is now expected to occur in cycles. We observed that the oscillation is influenced by sleep, food or physical effort. The results of the overcharging test of bilirubin are directly influenced by the cycle time of bilirubinemia; appearing even in normal subjects, inadequate testing, if implemented in periods of accumulation of bilirubin in the blood. Thus, the test of bilirubin loses its significance as an index of liver failure. The study of the various lesions of the liver, and its magnitude, found by the method of biopsies has allowed us to establish that there is no relationship between the anatomical deficiency of the liver and jaundice, provided the bile excretory pathways remain permeable. The clinical course of the various processes of liver pathology, studied directly related to the lesions found on biopsy, and not with the degree of jaundice. We have tried to divide the icterias into two groups: a) obstructive icterias, evolving, as Rich has shown, with injury to the bile canaliculi. b) icterias by increased hepatic threshold for excretion of bilirubin in the blood, which correspond to most icterias by Rich retention, evolving without compromise biliary excretory system. The threshold would increase liver conditioned by a process of the pyrrole nuclei economy to prevent loss of the intestinal tract, unable to be used in the re-synthesis of hemoglobin. Discussed the various mechanisms that produce this type of icterias. The jaundice that occurs in the group of hemolytic anemias, polycythemia in the height at "disease Monge" in newborns and has been discussed at some length, within the group of icterias by increasing the threshold liver for excretion of bilirubin.